Dysregulation of Cell Survival in Diffuse Large B Cell Lymphoma: Mechanisms and Therapeutic Targets - Miao, Yi; Medeiros, L. Jeffrey; Xu-Monette, Zijun Y.; Li, Jianyong; Young, Ken H. (Frontiers in Oncology, 2019)
Diffuse large B cell lymphoma (DLBCL) is the most common type of lymphoma worldwide, representing 30-40% of non-Hodgkin lymphomas, and is clinically aggressive. Although more than half of patients with DLBCL are cured by using standard first-line immunochemotherapy, the remaining patients are refractory to the first-line therapy or relapse after complete remission and these patients require novel therapeutic approaches. Understanding the pathogenesis of DLBCL is essential for identifying therapeutic targets to tackle this disease. Cell survival dysregulation, a hallmark of cancer, is a characteristic feature of DLBCL. Intrinsic signaling aberrations, tumor microenvironment dysfunction, and viral factors can all contribute to the cell survival dysregulation in DLBCL. In recent years, several novel drugs that target abnormal cell survival pathways, have been developed and tested in clinical trials of patients with DLBCL. In this review, we discuss cell survival dysregulation, the underlying mechanisms, and how to target abnormal cell survival therapeutically in DLBCL patients.